Epidemiological Profile and Clinicopathological Correlates of Triple Negative Breast Cancer Patients at Regional Cancer Centre - Verma, Richa; Lal Jakhar, Shankar; Sharma, Neeti; Kumar, H. S.; Beniwal, Surender (Asian Pacific Journal of Cancer Care, 2021)
Background: Breast Cancer is the most common cancer among woman worldwide. In India breast cancer remains the leading cause of both incidence and mortality. Triple negative breast cancer is more difficult to treat as it does not respond to hormone therapy medicines or medicines that target receptor proteins (like HER 2 Neu). It is crucial for the physician to know the status of the disease as the patient can be subjected to a whole new avenue of treatment. The present study was done to assess the epidemiological profile and clinicopathological correlates of patients of triple negative breast cancer. Material and Methods: This retrospective study was carried out in Acharya Tulsi Cancer and Research Institute located in the state of Rajasthan, Bikaner, India, among Ca Breast patients presenting to Medical Oncology, Radiation Oncology and Surgical Oncology outdoor & indoor from April 2016 to March 2017. Out of the total 1017 patients of carcinoma breast 957 were included in this Study. Exclusion criteria was non availability of ER, PR, HER2 neu status reports because of various reasons like affordability. Out of the total 957 patients 249 were found to be triple negative. Statistical analysis was done using IBM SPSS version 21. Results: Mean age of the patients was 46±11.23 years. Out of total 249 patients of triple negative breast carcinoma, 91 (%) were found to have had clinical staging I and II (Early stage) and 158 (%) patients were found to have clinical staging III & IV (Late Stage). Mean size of the tumor was 3.6±1.94cm. 151 (60.6%) were pre-menopausal, 103 (41.4%) and 12 (4.8%) patients had positive family history. All of or patients diagnosed to have Ductal type of carcinoma. Lympho-vascular invasion was seen in 51 (20.5%) patients and High grade Histological Grading was seen in High Grade 169 (67.9%) patients. 172 (69.1%) undergone MRM (Modified Radical Mastectomy) and BCS was done in 74 (29.7%) patients. After comparison of triple Negative Breast Cancer with non-triple Negative Breast Cancer, lower age, later stages (III and IV), pre-menopausal status and high grade (on histology) were significantly more in negative type of Ca breast. Occurrence of early Menarche (< 13 Years) and history of OC pills used was almost equal in both the groups. Conclusion: Triple Negative Breast Cancer was found to present at an earlier age and more in pre – menopausal women. Such patients presented with a higher histological grade of tumor and late stage of presentation. There was no statistically significant association between TNBC and age of menarche, use of OC pill, previous exposure to radiotherapy and positive family history in first degree relative.